ANALISIS KORELASI SEKTOR PERTANIAN TERHADAP TINGKAT KEMISKINAN DI PROVINSI SUMATERA UTARA - Adelia Octavia Sihombing; Rita Herawaty Bangun (Universitas Medan Area, 2019)
This study aims to analyze correlation of the agricultural sector on the level of poverty in North Sumatra Province. The data used are data on a gross domestic regional product (GDRP) according to the business field and the percentage of poor people during the years 2010-2017. The analytical method used in this study is a simple correlation analysis. The results showed that the agricultural sector variables significantly correlate poverty in North Sumatra but in a negative direction.